Identifying Opportunities and Challenges for Creating a Climate-Smart Food System in Vietnam - Baruah, Sampriti; Mohanty, Samarendu (2019)
This study examines various elements of food production, consumption, processing and distribution of food products in Vietnam to identify the challenges and opportunities for developing a sustainable and climate-smart food system. Both primary and secondary data are collected to analyze changing consumption pattern due to income growth and urbanization and identify constraints and opportunities of the current system. The results suggest that rice is already an inferior good for middle class and rich urban populations. These households are consuming more high value food products such as meat, dairy products, fruits, and vegetables. The positive and declining expenditure elasticities of rural population suggest that as income grows rural households will eventually start consuming less rice and more other food products. Since Vietnam’s economy continues to grow with doubling of GDP in the next decade, per capita rice consumption both in urban and rural and across different income will continue to decline.